An evaluation of Take Home Naloxone program implementation in British Columbian correctional facilities. Issue 1 (20th February 2019) - Pearce, Lindsay A.; Mathany, Lauren; Rothon, Diane; Kuo, Margot; Buxton, Jane A.
Abstract : Purpose: To understand how the Take Home Naloxone (THN) program is implemented in two pilot correctional facilities in British Columbia (BC), Canada, in order to identify areas for program improvement and inform the expansion of the program to other Canadian correctional facilities The paper aims to discuss these issues. Design/methodology/approach: Two focus groups and one interview were conducted with healthcare staff at two pilot correctional facilities. Sessions were audio recorded, transcribed verbatim and divergent and convergent experiences within and between the facilities were explored in an iterative process. Key themes and lessons learned were identified and later validated by focus group participants. Findings: Key themes that emerged included: challenges and importance of the train-the-trainer program for healthcare staff conducting participant training sessions; potential for improved prison population engagement and awareness of the program; tailoring program resources to the unique needs of an incarcerated population; challenges connecting participants to community harm reduction resources following release; and clarifying and enhancing the role of correctional officers to support the program. Research limitations/implications: The correctional setting presents unique challenges and opportunities for the THN program that must be considered for program effectiveness. Originality/value: This evaluation was conducted to inform program expansion amidst a historic opioid overdose epidemic in BC, and adds to the limited yet growing body of literature on the implementation and evaluation of this program in correctional settings globally.